Innovative equipment to monitor and control salt usage when cooking at home: iMC SALT research protocol for a randomised controlled trial - Gonçalves, C (2020)
Introduction. Excessive salt intake is a public health concern due to its deleterious impact on health. Most of the salt consumed come from those that are added when cooking. This study will improve knowledge on the effectiveness of interventions to reduce salt consumption among consumers. Methods and analysis. In this randomised clinical trial, we will be evaluating the efficacy of an intervention—the Salt Control H, an innovative prototype equipment to monitor and control use of salt when cooking—among workers from a public university, with the aim of reducing their dietary salt intake. We will randomly select 260 workers who meet the eligibility criteria and who are enrolled to an occupational health appointment and randomise them into one of the two arms of the study (either control or intervention), with matched baseline characteristics (sex and hypertension). The intervention will last for 8 weeks, during which the participants will use the equipment at home to monitor and control their use of salt when cooking. The main outcome will be 24-hour urinary sodium excretion at baseline, at fourth and eighth weeks of intervention, and at 6 months after intervention. Ethics and dissemination. Ethical approval for the study has been obtained from the Ethics Committee of the Centro Hospitalar Universitário São João. The results of the investigation will be published in peer-reviewed scientific papers and presented at international conferences.